Chemotherapy in the Elderly: Translation of Hurria's Toxicity Score to Portuguese - Lucíola de Barros Pontes; Lessandra Chinaglia; Theodora Karnakis; Juliana Todaro; Heloisa Veasay Rodrigues; Polianna Mara Rodrigues de Souza; Ludmila de Ol iveira Koch; Rafael Aliosha Kaliks Guendelmann; Auro del Giglio (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To describe the translation and transcultural adaptation of Hurria's chemotherapy toxicity score, a prediction tool to estimate chemotherapy toxicity in the elderly. METHODS: The original English version of the score was translated to Portuguese using the forward and backward translation technique, as described by Guilemin. RESULTS: The translation was performed by two Brazilians (a physician and a professional translator), both fluent in English. Two professionals from a specialized linguistic service, not related to the study, then carried out the backward translation. Finally, a medical committee composed of oncologists, geriatricians, and hematologists discussed the consistency of the score, choosing a final version of the instrument in Portuguese. This version was piloted-tested in medical charts in an Oncogeriatric service, with high reliability as tested by Kappa statistic test. CONCLUSION: The final version of Hurria's chemotherapy toxicity score in Portuguese proved to be an easy, clear, and quick tool, suitable for use in clinical practice.